The effect of a social reintegration (parole) program on drug-related prison inmates in Japan: a 4-year prospective study - Yokotani, Kenji (Asian journal of criminology, 2017)
Social reintegration has been known to protect against recidivism, but its effects against drug-use relapse have previously remained unclear. To address this gap, the present study sampled 196 inmates imprisoned for drug-related offenses in Japan. We examined the protective effects of a social reintegration (parole) program against recidivism and drug-use relapse using a 4-year prospective design. During the 4-year follow up, 79 (40.3 %) of the participants reoffended and 61 (31.1 %) relapsed into drug use. The results suggest that the parole program was significantly associated with a decreased risk of recidivism, even if participants’ age, sentence length, number of prison terms, educational levels, and gang membership were controlled for. However, the effects of the parole program on drug relapse disappeared when the above variables were controlled for. To decrease the risk of relapse, drug-related inmates may need both prosocial communities and rehabilitative environments. The Japanese criminal justice system needs to introduce drug treatment courts for drug users.